Strengthening Digital Character and Social Skills Through Board Games in Social Impact Informatics Learning - Puji, Nunuk Riza; Sutopo, Yeri; Supraptono , Eko; Arief, Ulfah Mediaty (International Journal of Active Learning, 2025)
This study aims to develop Game-Based learning media, specifically a board game, as an innovative strategy to strengthen students' digital character and social skills in the context of the Social Impact of Informatics material. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation), with high school students as research subjects. The learning media were designed based on the learning outcomes of the Independent Curriculum with a focus on digital ethics, information literacy, and social responsibility as digital citizens. Validation results from material and media experts indicate that the developed board game media is feasible to use. Practical tests conducted by teachers and students demonstrated a high level of ease of use, clarity of instructions, attractiveness, and learning benefits. The effectiveness of the media was tested using a pretest-posttest design with N-Gain analysis and an independent t-test, which showed a significant increase in students' cognitive abilities and social attitudes. Observations during the learning process also strengthened aspects of cooperation, empathy, responsibility, and ethical reflection on the use of technology. This board game has been proven to facilitate cognitive understanding of the Social Impact of Informatics and foster wise digital character and relevant social competencies in the digital age. These findings contribute to contextual and meaningful informatics learning practices and offer a practical solution for values education in the digital transformation era.